MENEGUHKAN KESETARAAN GENDER YANG BERKEADILAN DALAM ISLAM - Ayub Mursalin (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2020)
Gender inequity is not the failure subjected to the Prophet Muhammad. The interpretations, thoughts, legal opinions, imaginations of His successors were the causes of the bias as they interpreted the Holy Qur’an and the Sunnah based on the prevailing facts and situation when the Qur’an was revealed, at the time. To reinterpret the doctrinal teachings which allegedly considered bias, one can use many approaches, namely hermeneutical and historical and other comprehensive ones. The result of this endeavor is a living-text function as the guidance for a forever life of human beings.